2021
DOI: 10.1093/cvr/cvab133
|View full text |Cite
|
Sign up to set email alerts
|

The voltage-gated potassium channel KV1.3 regulates neutrophil recruitment during inflammation

Abstract: Aims Neutrophil trafficking within the vasculature strongly relies on intracellular calcium signaling. Sustained Ca2+ influx into the cell requires a compensatory efflux of potassium to maintain membrane potential. Here, we aimed to investigate whether the voltage-gated potassium channel KV1.3 regulates neutrophil function during the acute inflammatory process by affecting sustained Ca2+ signaling. Methods and results Using i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 58 publications
0
20
1
Order By: Relevance
“…Moreover, a recent electrophysiological study strongly supports that the cells we classified as PMN-MDSCs are different from neutrophils. Using electrophysiological assays, Immler and co-workers have shown that neutrophil polymorphonuclear leukocytes (PMN) functionally express voltage-gated Kv1.3 K + channels [ 61 ], in clear contrast to our whole-cell records, where Kv1.3 or any other voltage-gated K + current was missing.…”
Section: Discussioncontrasting
confidence: 58%
“…Moreover, a recent electrophysiological study strongly supports that the cells we classified as PMN-MDSCs are different from neutrophils. Using electrophysiological assays, Immler and co-workers have shown that neutrophil polymorphonuclear leukocytes (PMN) functionally express voltage-gated Kv1.3 K + channels [ 61 ], in clear contrast to our whole-cell records, where Kv1.3 or any other voltage-gated K + current was missing.…”
Section: Discussioncontrasting
confidence: 58%
“…However, neutrophil depolarisation could also produce a robust Ca 2+ rise that was insensitive to APV (Fig. 1H), confirming the additional, voltage-dependent and NMDAR-independent routes of Ca 2+ entry, such as the voltage-gated Ca 2+ channel Kv1.3 32 .…”
Section: Resultsmentioning
confidence: 54%
“…Aquaporins (AQP3 and AQP4) and GABRA1 are also induced in response to bacterial infection, functioning in proinflammatory pathways and the enhancement of antimicrobial responses respectively [27,28]. Several genes are also associated with immunoregulation, including KCNA3, which is a critical regulator of neutrophil function and promotes chemotaxis and phagocytic mechanisms [29], as well as CCK, which can be expressed by leukocytes and modulates the local and systemic inflammatory response, chemotaxis and bactericidal capacity [30,31]. Collectively, we postulate that depletion of these genes in AI-DRFUs relative to CI-DRFUs is owing to bacterial mechanisms that disrupt host cellular/immune homeostasis and cause pathogenesis.…”
Section: Discussionmentioning
confidence: 99%